2013
DOI: 10.1111/nph.12538
|View full text |Cite
|
Sign up to set email alerts
|

Determining place and process: functional traits of ectomycorrhizal fungi that affect both community structure and ecosystem function

Abstract: SummaryThere is a growing interest amongst community ecologists in functional traits. Response traits determine membership in communities. Effect traits influence ecosystem function. One goal of community ecology is to predict the effect of environmental change on ecosystem function. Environmental change can directly and indirectly affect ecosystem function. Indirect effects are mediated through shifts in community structure. It is difficult to predict how environmental change will affect ecosystem function vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
219
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(223 citation statements)
references
References 60 publications
4
219
0
Order By: Relevance
“…Accordingly, it has been suggested that melanin contributes to C storage in soils (5), eventually accumulating as humic material (163,177,179). In consideration of these properties, Koide et al (42) proposed melanin production as a fungal trait that may form a direct link between environmental stress and ecosystem function.…”
Section: Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it has been suggested that melanin contributes to C storage in soils (5), eventually accumulating as humic material (163,177,179). In consideration of these properties, Koide et al (42) proposed melanin production as a fungal trait that may form a direct link between environmental stress and ecosystem function.…”
Section: Stress Tolerancementioning
confidence: 99%
“…Although they can act as "decomposers in disguise" (reviewed in reference 249), their capacity for breakdown of complex organic C is relatively low (115,250). In addition, ectomycorrhizal root tips and rhizomorphs can be long-lived and slow to decompose (45,(251)(252)(253)(254)(255)(256)(257), which can contribute to microbial immobilization of C, N, and P. Altogether, mycorrhizal fungi may augment soil C storage (30,42,255,258,259). Moreover, their abundance is influenced not only directly by climate and nutrient availability but also by the presence and activities of host plants (260)(261)(262).…”
Section: Figmentioning
confidence: 99%
“…EM fungi play a significant role in global nutrient and carbon cycles by enhancing the nutrient and water uptake by trees and absorbing carbon from their hosts (Smith and Read, 2008). Temperate and boreal forests, which cover B14% of the land surface (FAO, 2012), harbor hundreds of taxonomically and functionally diverse EM fungi (Read and PerezMoreno, 2003;Tedersoo et al, 2010;Koide et al, 2014). Recent environmental change may have altered fungal communities, which would subsequently affect the associated plant communities and ecosystem functioning (Parrent et al, 2006;Johnson et al, 2013;Dickie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite generally broad enzymatic capacities (6), not all ECM fungi have the ability to access peptide N, which has resulted in the classification of ECM fungi into "protein" and "nonprotein" species (7). Multiple authors have suggested that natural selection should favor traits allowing mycorrhizal fungi to utilize the most abundantly available N source in their environment (8). This would suggest that protein ECM fungal species have their ecological niche in organic-N-rich soils.…”
mentioning
confidence: 99%